Neurological effects of product price and evaluation on online purchases based on event-related potentials. (21st June 2019) - Tang, Xiaoli; Song, Zhijie
Highlights: The neural process of decision-making was revealed when shopping online on the basis of price and evaluation rating. The cognitive stages comprise early automatic perceived stage, later evaluation stage and evaluative categorization stage. High evaluation ratings induced positive responses. Evaluation ratings were considered to be a high-scope cue that warranted more cognitive resources. Abstract: In order to better understand how price and evaluation impact consumers' decision making, this research examined the neural bases underlying consumers' cognition of the two important clues when shopping online. An ERP experiment was conducted involving 19 Chinese students and the behavior data revealed that product price and evaluation significantly influenced their willingness to purchase mobile phones online, and the speed with which they made purchase decisions supported cue-diagnosis theory. Further, ERP results indicated three neural stages of decision-making: early automatic cognition with emotional valence and negativity bias effects elicited by product evaluation ratings, an evaluation stage exhibiting an attention, and a final stage featuring an evaluation–categorization pattern associated with pleasurable sensations. Specifically, those three neural stages of online decision-making were coded with corresponding event-related potentials in brain, that is, N1 and P2 in automatic cognition stage, P300 in evaluation phase, LPP in concluding phase. Hence, the research results reveal neurological effects of product price and evaluation on online purchases and deepen our comprehension of consumers' cognitive process.